The Role of Exosomal miRNAs in Promoting Tumor Metastasis: A Molecular Insight - Kumar, Nitish; Negi, Anup; Mehra, Diksha; Khan, Farah (Journal of Neonatal Surgery, 2025)
Exosomal miRNAs, such as miR-21, miR-10b, and miR-210, play critical roles in tumor progression, particularly in promoting metastasis through tumor microenvironment modulation, immune evasion, and angiogenesis. This study examines the molecular mechanisms and cross-national variability in exosomal miRNA expression linked to metastatic potential across diverse cancer types. We collected exosomal samples from breast, lung, and colorectal cancer patients at various metastatic stages from three countries. Quantitative RT-PCR assessed the expression levels of miR-21, miR-10b, and miR-210. Statistical analyses, including correlation tests and multivariate models, were employed to explore the relationship between miRNA levels and metastatic stages. Elevated levels of miR-21 and miR-210 were positively correlated with increased metastatic potential across all cancer types. Notably, miR-21 showed significant association with advanced stages in breast and colorectal cancers, while miR-210 was predominantly elevated in lung cancer metastases. Cross-national analyses revealed variances in miRNA expression, suggesting potential influences of genetic and environmental factors. Our findings underscore the pivotal role of exosomal miRNAs as both biomarkers and active facilitators of tumor metastasis. The cross-national differences highlight the need for personalized approaches in cancer treatment. Future studies should focus on targeted miRNA inhibition strategies and explore environmental factors affecting miRNA expression.